2022
DOI: 10.1038/s42005-022-00858-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order motif analysis in hypergraphs

Abstract: A deluge of new data on real-world networks suggests that interactions among system units are not limited to pairs, but often involve a higher number of nodes. To properly encode higher-order interactions, richer mathematical frameworks such as hypergraphs are needed, where hyperedges describe interactions among an arbitrary number of nodes. Here we systematically investigate higher-order motifs, defined as small connected subgraphs in which vertices may be linked by interactions of any order, and propose an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 84 publications
0
42
0
Order By: Relevance
“…Secondly, higher-order networks provide greater social context to observed associations or interactions. For example, it might be of interest to distinguish if an individual participating in group interactions also forms connections with those individuals in smaller, pairwise, contexts, an insight which can be obtained through higher-order motif analysis (Lotito et al 2022). Similar reasoning applies to the mesoscale properties of a networked society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, higher-order networks provide greater social context to observed associations or interactions. For example, it might be of interest to distinguish if an individual participating in group interactions also forms connections with those individuals in smaller, pairwise, contexts, an insight which can be obtained through higher-order motif analysis (Lotito et al 2022). Similar reasoning applies to the mesoscale properties of a networked society.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher-order motif analysis (Lugo-Martinez et al . 2021; Lotito et al . 2022) revealed that clustered pairwise collaborations among scientific authors are predictive of future 3-way interactions (Benson et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe weak evidence that more efficient markets have more stable structures. We study how simplicial motifs—patterns of edges which define simplicial complexes on a graph [ 26 , 27 ], e.g., edges, triangles and tetrahedra—are persisting or decaying through the time evolution of the filtered networks computed over a rolling time window. In order to test the multivariate long memory properties of financial time series, we compare the motif persistence in networks from real data with motif persistence from a range of null models [ 28 ]—corresponding to a range of parsimonious assumptions on the underlying generative processes—for groups of time series.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al emphasized that it is important to consider the non-Markovian process when modeling sequential data and proposed a higher-order network representation and algorithm [ 18 , 34 ]. Lotito et al defined higher-order motifs as small connected subgraphs in which vertices may be linked by interactions of any order and proposed an efficient algorithm to extract complete higher-order motif profiles from empirical data [ 35 ]. Aktas et al proposed two new Laplacians that allowed redefining classical graph centrality measures for higher-order interactions [ 36 ].…”
Section: Introductionmentioning
confidence: 99%